Analysis of the Effect of Social Capital, Cultural Capital And Symbolic Capital On Interest in Entrepreneurship with Self- Efficacy - Andarweni Astuti; Eva Banowati; DWP Sucihatiningsih; Rusdarti Rusdarti (International Conference on Science, Education, and Technology, 2023)
Entrepreneurship education at universities has been carried out through classroom learning, as well as through campus programs such as PKM K. These efforts sometimes reap success but sometimes also fail. Failure can be caused by student interest, background in participating in activities in order to get maximum grades so that in the end the university's efforts are not able to arouse students' enthusiasm to become entrepreneurs, this has an impact on the number of relaxations which has shown an increasing trend in the last 5 years. The purpose of this study was to examine how much social capital, cultural capital and symbolic capital of STPKat St. Francis of Assisi Semarang students influence the interest in entrepreneurship with self-efficacy. The analytical method used is path analysis and simple linear regression analysis. This type of research is quantitative research, the independent variables are social capital, symbolic capital and cultural capital possessed by students in entrepreneurship, and the dependent variable is entrepreneurial interest with self-efficacy. The sample used is 30 students. The results obtained are that social capital, cultural capital and symbolic capital only have an effect of 28.7%, while 71.3% are influenced by other variables.